DOI: 10.1007/978-3-540-74851-9_32
|View full text |Cite
|
Sign up to set email alerts
|

Know Thy Sensor: Trust, Data Quality, and Data Integrity in Scientific Digital Libraries

Abstract: Abstract. For users to trust and interpret the data in scientific digital libraries, they must be able to assess the integrity of those data. Criteria for data integrity vary by context, by scientific problem, by individual, and a variety of other factors. This paper compares technical approaches to data integrity with scientific practices, as a case study in the Center for Embedded Networked Sensing (CENS) in the use of wireless, in-situ sensing for the collection of large scientific data sets. The goal of th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
45
0
21

Publication Types

Select...
9

Relationship

5
4

Authors

Journals

citations
Cited by 54 publications
(67 citation statements)
references
References 12 publications
1
45
0
21
Order By: Relevance
“…This echoes the work of Wallis et al [37] (p. 380), which has examined the criteria for "users to trust and interpret the data in scientific digital libraries". In a recent publication, Borgman et al [38] have described the outcomes from a project which explored the ability of the so-called "long tail" of researchers, as exemplified by small and medium sized laboratories (SMLs), to manage their data.…”
Section: Trust In Research Datasupporting
confidence: 52%
“…This echoes the work of Wallis et al [37] (p. 380), which has examined the criteria for "users to trust and interpret the data in scientific digital libraries". In a recent publication, Borgman et al [38] have described the outcomes from a project which explored the ability of the so-called "long tail" of researchers, as exemplified by small and medium sized laboratories (SMLs), to manage their data.…”
Section: Trust In Research Datasupporting
confidence: 52%
“…Furthermore, the ability of a scientist to assess the integrity and trustworthiness of a dataset tends to be enhanced when the scientist has greater knowledge about the factors-both social and technical-involved in the different stages of the dataset's production and curation [54]. Our CENS findings show that the production and use of multiple types of datasets significantly complicate these issues.…”
Section: Discussionmentioning
confidence: 91%
“…Our research on CENS found that scientists' ability to assess the integrity of data was essential for reuse. This ability depended on the knowledge the scientist possess of stages of the data life cycle-from research design to data storage and curation [54]. The life cycle of CENS data involved many steps, each dependent on preceding steps: the effect of decisions made at each step was cumulative throughout the life cycle [53].…”
Section: Trust In Datamentioning
confidence: 99%
“…Spreadsheets often suffice for data management and analysis, especially if the number of observations and data elements is small. Spreadsheets may be the lowest common denominator among small research groups, and provide the means for data exchange within or between teams [35]. At the other end of this dimension are the large repositories necessary to manage the flood of data from telescopes, particle detectors, and other research instruments.…”
Section: Methods Of Data-driven Researchmentioning
confidence: 99%